2007
DOI: 10.1353/cpr.2007.0017
|View full text |Cite
|
Sign up to set email alerts
|

Personal Care Assistants and Blood Exposure in the Home Environment: Focus Group Findings

Abstract: Focus group findings will be used to implement a union-based participatory primary prevention intervention for the reduction of blood exposure among PCAs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 6 publications
0
9
0
Order By: Relevance
“…Although the survey question was limited to health problems, it is not unreasonable to think that they neither received information on client history of previous violence, mental illness or substance abuse before they saw their clients. DCWHs have reported that they felt vulnerable when they were not informed of clients’ contagious health condition [Zanoni et al, ]. Having no or limited information for potential hazards before meeting clients for the first time may put DCWHs at a very high risk of being a victim of violence.…”
Section: Discussionmentioning
confidence: 99%
“…Although the survey question was limited to health problems, it is not unreasonable to think that they neither received information on client history of previous violence, mental illness or substance abuse before they saw their clients. DCWHs have reported that they felt vulnerable when they were not informed of clients’ contagious health condition [Zanoni et al, ]. Having no or limited information for potential hazards before meeting clients for the first time may put DCWHs at a very high risk of being a victim of violence.…”
Section: Discussionmentioning
confidence: 99%
“…Some activities with the potential for bloodborne contact (e.g., changing wound dressings or giving injections) are outside the formal PCA scope of practice. However, both qualitative [Zanoni et al, 2007] and quantitative data demonstrate that the tasks for which PCAs are responsible often involves handling contaminated dressings or needles. For example, bathing an individual with a wound will often require removal and replacement of bandages, changing linens and clothing that may be contaminated with blood, and clients who use needles or lancets may not dispose of them properly [Beltrami et al, 2000;Markkanen et al, 2007;Chalupka et al, 2008].…”
Section: Discussionmentioning
confidence: 99%
“…Despite the variation in services and providers in home care, certain features of home care are similar for all workers; that is, workers travel to and provide care in clients' homes, creating significant limitations on their ability to control the work environment. The usual features of an institutional work setting are absent such as security, housekeeping, standard room configurations and bed types, and on-site colleagues and supervisors [Zanoni et al, 2007]. Also, standard healthcare environmental hazard controls such as needle disposal systems and safety-engineered needles and sharps may not be available.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A small but growing literature indicates that HCAs face challenging working conditions such as job demands, lack of respect and isolation, and hazardous exposures ranging from slips, trips, and falls to sharps injuries and blood/body fluid exposure. 1015…”
mentioning
confidence: 99%